The Influence of Creativity and Self-Confidence on Craft and Entrepreneurship Learning Outcomes in Bunda Auni Vocational School Students Bekasi - Hugo Aries Suprapto (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Entrepreneurship has become an important topic in Asian countries. Indonesia's labor index is still low, and below other countries such as Vietnam. The creativity and self-confidence of vocational school students need to be encouraged. The aim of this research is to determine the influence of creativity and self-confidence on the crafts and entrepreneurship of Bunda Auni Vocational School students. The method used is a quantitative method. Data was taken by filling out questionnaires and interviews. The results of the research show that there is an influence of creativity and self-confidence on the crafts and entrepreneurship of Bunda Auni Vocational School students. It is recommended that schools create special programs to improve students' soft skills, so that they are ready to compete to become young and tough entrepreneurs.